Dietary Quercetin Reduces Plasma and Tissue Methylglyoxal and Advanced Glycation End Products in Healthy Mice Treated with Methylglyoxal. Issue 9 (5th June 2021) - Zhao, Yantao; Tang, Yao; Sang, Shengmin
ABSTRACT: Background: Methylglyoxal (MGO), a precursor of advanced glycation end products (AGEs), has been linked to AGEs-associated diseases. Objectives: This study investigated the efficacy and mechanisms of dietary quercetin in decreasing plasma and tissue concentrations of MGO and AGEs in MGO-administered mice. Methods: Male, 6-wk-old CD-1 mice were administered AIN-93G diet and water (Con) or 0.12% MGO in water (MGO) or MGO plus 0.2% (0.2Q) dietary quercetin for 1 wk ( n = 5) (experiment 1), and water (Con), 0.12% MGO (MGO), or MGO plus 0.1% (0.1Q), 0.2% (0.2Q), or 0.4% (0.4Q) dietary quercetin for 6 wk ( n = 10) (experiment 2). The plasma, kidney, and liver concentrations of MGO, quercetin, and isorhamnetin and their trapping adducts with MGO were determined by LC-MS, and AGE concentrations were measured by the fluorescent method. Furthermore, the expressions of glyoxalase I/II (GLO I/II) and aldose reductase (AR), MGO detoxification enzymes, were determined by Western blot. One-factor ANOVA and post hoc Dunnett's or Tukey's test were used to analyze the data. Results: After 1 wk of treatment, the MGO concentrations in plasma (20.2%) and kidney (29.9%) in 0.2Q mice were significantly lower than those in MGO mice. After 6 wk of treatment, the concentrations of MGO in the plasma (14.7–18.6%), kidney (20–20.8%), liver (15.4–18.6%), and tissue AGEs (28–36.8%) in 0.1Q, 0.2Q, and 0.4Q mice were significantly lower than those in MGO mice. The plasma concentrations of quercetin, isorhamnetin, and their MGO adducts were dose-dependently increased after quercetin administration. In addition, after 6 wk of quercetin administration, the expressions of GLO I/II and AR in the liver and kidney were significantly upregulated to promote MGO detoxification compared with MGO-treated mice. Conclusions: Quercetin reduced plasma and tissue MGO concentrations and inhibited AGE formation by trapping MGO and regulating the MGO detoxification systems in MGO-administered healthy mice.